2016
DOI: 10.1111/bjh.14167
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cell transplantation for sickle cell disease – current practice and new approaches

Abstract: Sickle cell disease is an inherited disorder that affects over 5 million people worldwide. Current maintenance therapy has been successful in reducing complications and enhancing life expectancy; yet subclinical complications persist. To date, allogeneic haematopoietic stem cell transplant (HSCT) remains the only available curative therapy for sickle cell disease. With declining incidences of rejection and transplant- related mortality, disease-free survival after human leucocyte antigen-identical sibling tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 70 publications
(96 reference statements)
0
39
0
2
Order By: Relevance
“…11 Although several reports have demonstrated that HLA-identical sibling transplantation with bone marrow (BM) or umbilical cord blood (CB) establishes normal hematopoiesis and is associated with excellent survival, most studies were conducted at single institutions or in the context of clinical trials. [12][13][14][15][16][17] The current study sought to describe outcomes after HLA-identical sibling transplantation for SCD worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…11 Although several reports have demonstrated that HLA-identical sibling transplantation with bone marrow (BM) or umbilical cord blood (CB) establishes normal hematopoiesis and is associated with excellent survival, most studies were conducted at single institutions or in the context of clinical trials. [12][13][14][15][16][17] The current study sought to describe outcomes after HLA-identical sibling transplantation for SCD worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] HLAmatched sibling donor transplants account for the majority of transplants performed worldwide for hemoglobinopathy. 6,7 However, only 18% of patients with SCD have an HLA-matched sibling donor in the United States. 8 HLA-matched adult unrelated donors (URDs) have been used to expand the donor pool for nonmalignant hematologic disorders, but their role in SCD transplants is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, ,1 in 10 of these families will have to cope with the major adverse outcome of BMT transplant-related mortality (TRM) and severe chronic graftversus-host disease (GVHD). 2,3 Given that SCD causes premature death and disability, particularly in young adults, and has a major impact on the quality of life for patients at all ages and their families, 4 these are convincing results. Can similarly impressive results be achieved for the 80% to 90% of patients with SCD who do not have HLA-matched family donors?…”
Section: Imperial College Healthcarementioning
confidence: 99%
“…2,3 Overall, the outcome is extremely good, and BMT remains the best immediate prospect for long-term cure for children who are currently experiencing severe sickle-related complications. 2,3 Compared with other disease-modifying therapies, such as regular transfusion and hydroxycarbamide, matched related donor BMT will not only stop ongoing vaso-occlusive crises and arrest progressive organ damage in most cases, but may also lead to regression of damage in some cases. 3 Aggregate results from case series and clinical trials show disease-free survival of ;92% and overall survival (OS) of ;95% of children and young adults with SCD with a matched sibling donor.…”
Section: Imperial College Healthcarementioning
confidence: 99%
See 1 more Smart Citation